COMPUTED TOMOGRAPHY IN KAWASAKI DISEASE DIAGNOSIS AND LONG-TERM FOLLOW-UP: CASE REPORT - Rodrigo Beraldo, Sergio; Talita Brezger Santos, Amy; Clara Beraldo Muniz, Ana; Maria Ribeiro de Oliveira, Gabriela; Azevedo Cardeliquio Cantarelli, Isadora; Carlos Boschi Neto, José; de Oliveira Chagas, Julia; Sartorio Sant’Ana, Hygor; Lemos Ferreira Andrade Paiva, Renan; Barbosa da Costa Pimenta Duarte, Sasha (Health and Society, 2023)
Kawasaki disease (KD) is a disease that causes inflammation in blood vessels and can lead to serious heart problems, such as aneurysms. It is important to identify the disease quickly so that preventative measures can be taken. The main symptoms include fever, red eyes, swollen and red tongue, redness and swelling of the hands and feet, and swollen lymph nodes. If you notice these symptoms, seek medical attention immediately. Coronary CT angiography is a very effective test for detecting the presence of aneurysms and other cardiac complications in KD. Treatment includes immunoglobulin and aspirin, which help reduce inflammation in the blood vessels and minimize the risk of serious heart problems. To ensure good heart health in the long term, it is important to have regular follow-up with a cardiologist and undergo additional tests, such as exercise test, to monitor the evolution of the disease. If diagnosed early, KD can be treated successfully and prevent serious complications.